Pengaruh Pendekatan Problem Solving Terhadap Kemampuan Penalaran Matematis Siswa Kelas V Sekolah Dasar - Dwi Widyastuti Nurharyanto; Jailani Jailani (Universitas Khairun, 2023)
This study aims to describe the effect of the Problem Solving approach on the mathematical reasoning abilities of Class V Elementary School students. This research is a quasi-experimental research using one experimental class and one control class. One experimental class, namely SDN Rejondani with a problem solving approach and one control class that was not given treatment, namely SDN Potrojayan II. Learning achievement and mathematical reasoning abilities are measured using test instruments in the form of short answer questions and essay questions. Hypothesis testing using one way ANOVA univariate test. The results showed that problem solving had an effect on mathematical reasoning abilities with a significance value of 0.014 (p > 0.05).